Gender Dysphoria in When The Moon Was Ours Novel By Anna Marie Mclemore - rahmat fajar; tira mariana; utami rizki abdillah (English Language, Linguistics, Literature, And Education Journal, 2022)
This research discusses gender dysphoria in When the Moon Was Ours novel by Anna-Marie McLemore as reflected by the main character named Samir. Samir was born as a girl called Samira who got an uneasy feeling with his gender identity. Gender dysphoria is uneasy feeling associated with the incongruence wherein gender identity does not match one‟s biological sex. This research aims to find out the characteristics, the causes and the impacts of gender dysphoria in the novel. In this research, the writer uses the theory by the American Psychiatric Association to ensure characteristics and impacts of gender dysphoria and another theory by Susan Stryker to determine its causes. The writer also uses Queer theory as proponent in formulating problems. Kind of research is library research with descriptive qualitative methods. Source of data of the research is a novel, several sources of journal, books and articles related to this thesis. Research findings shows that first, gender dysphoria characteristics experienced by main character tends to inconsistency between sex and gender identity, a desire to erase the primary or secondary sex characteristics, a desire to have primary or secondary sex characteristics of the other gender, a desire to be a figure of the other gender, a desire to be treated as the other gender and a desire to have typical feeling as the other gender. The second, causes of gender dysphoria is due to social and cultural factors, it contains a Pakistani tradition called Bacha Posh and the emotional dynamics he had in his family.The last, the impacts of gender dyphoria are anxiety disorder, suicide attempts, functioning at school may disturbed, stigmatization, discrimination and tends to get negative self-concept.